Evaluating the Role that Monastic Educational Principles Play in Education in Monastic Boy Schooling in Gauteng Province, South Africa - Gradidge Jason; Sepeng Mmalefikane Sylvia (Discourse and Communication for Sustainable Education)
Monastic education has a rich history rooted in discipline, community, intellectual pursuits and spirituality. Every year, parents all over South Africa are posed with the question of selecting a school for their children. This article aims to evaluate the role of monastic educational principles in shaping the educational experiences within monastic schools. In a modern context, these principles continue to play a significant role in the development of students within monastic schools nurturing well-rounded learners for life after school. This paper adopted a qualitative approach and included a total of 12 participants from four schools. The principals and two department heads from each school were chosen to provide a thorough evaluation of the role that monastic educational principles play in education in monastic schools. By examining and exploring the ways in which monastic educational principles are implemented, this article highlights the enduring influence of monastic traditions in education and underscores their relevance in preparing young men for a well-rounded and meaningful life. This article was authored to assist with the understanding of the value that these kinds of schools have in our educational system. It is evident from the findings and affirmations of the participants that there are both advantages and disadvantages when evaluating the role monastic educational principles play in education in monastic schools. The recommendations of the study include that there should be a strong emphasis by teachers, department heads and principals on the application of monastic principles as there is a direct link to strong academic performance.